STUDI ETNOBOTANI TUMBUHAN OBAT PADA MAYARAKAT KAILI RAI DI DESA TARIPA KECAMATAN SINDUE KABUPATEN DONGGALA SULAWESI TENGAH - Sri Wahyuni A. Bana; Akhmad Khumaidi; Ramadhanil Pitopang (Biocelebes, 2016)
This study aims to document the types of medicinal plants, how to use medicinal plants, the type of disease that can be cured, and perentase habitus herbs are used daily by the village community Taripa village and to utilization. This study was conducted in April-May 2014. The method used in this study is a combination of qualitative research methods and quantitative research. Recorded 41 species from 28 families were used by villagers Taripa as medicine. The cooking methods, namely by boiling, crushed, chewed, squeezed, the topical and sliced. Organs of traditional medicinal plants in use are the leaves, roots, stems, roots, rhizomes, fruits, bark, and stem. Plant organs most widely utilized is the percentage of leaves with the use of 63 %. The percentage of plants that use and know ledge of the highest of orange (Citrus aurantifolia) by 98 % and the lowest percentage is hiptis (Hyptis capitata) Only by 16 %. Keywords: Medicinal plants, ethnobotany, taripa village